Estudo do envelhecimento da liga AA 7075 encruada - Barros, Felipe da Silva [UNESP] (2013)
Aluminum alloys are widely used in industry, because they combine different mechanical properties according to the alloying elements used in addition to thermal and mechanical treatments performed, resulting in materials with good weight/resistance relation. The 7XXX series alloys are worked heat treatable alloys commonly used in the aerospace industry, especially due to their high mechanical properties obtained after aging heat treatment, which increases the interest around 7075 alloy. Some studies with alloys which can be aged show that it is possible that cold word processes affect the results of aging. Thus, this study was intended to verify the influence of the aging process of AA 7075 alloy. There were three routes of aging with specimens previously treated thermally. In the first route T6 treatment was performed with a annealed specimen and other in solid solution. The second was the natural aging in a annealed specimen. In the last route was done aging by steps with a annealed specimen and other in solid solution with the intention to reduce the effects of natural aging. The results show that the routes 1 and 3 had similar hardness for all the samples, showing that the validity of Route 3 as an alternative and also the hardening did not affect the hardness at the end of the process, significantly reducing the time required for the highest hardness. Finally, natural aging was less effective in increasing hardness